265 BK-Virus Positive Invasive High-Grade Urothelial Carcinoma in an 8-Year-Old Renal Transplant Recipient With BK Virus Nephropathy. (11th January 2018) - Ahn, Meejin; Van Batavia, Jason; Kolon, Thomas; Schwartz, Lauren; Pogoriler, Jenny
Abstract: Introduction: Urothelial carcinoma is extremely rare in children and may be fundamentally different than in adults. Fewer than 30 cases have been reported in patients under 10 years old. BK polyomavirus infection is a major problem in transplantation, especially in renal transplant recipients. According to literature, 1%-10% of renal transplant recipients develop polyomavirus-associated nephropathy. The possibility that BK polyomavirus may be carcinogenic in humans is controversial, but SV40 large T antigen is known to inhibit tumor suppressors pRB and p53, and to transform some cell lines in culture. Adult renal transplant recipients have a 3-5x increased risk of urothelial carcinoma. Methods: The cystoprostatectomy specimen from an 8-year-old boy with a history of renal transplantation was processed according to standard procedure, and evaluated using H&E and immunohistochemical stains (IHC). Additional ancillary testing included molecular studies for BK virus using PCR for VP1 and identity testing using HLA typing. Results: The patient was an 8-year-old ex 32-week gestation twin boy with a history of chronic kidney disease and developmental delay. He had end-stage renal disease of unclear etiology and underwent kidney transplantation five years earlier from a living non-related donor who was a smoker. He had been immunosuppressed since transplantation, and his course was complicated by uncontrolled BK viremia and BK nephropathy despite prolonged treatment. Five years after his renal transplant, he was noted to have gross painless hematuria. Biopsy of a bladder lesion showed high-grade urothelial carcinoma, and ureteroscopy of native and transplant ureters showed no gross malignancy. He underwent cystoprostatectomy and bilateral native nephroureterectomies with cutaneous ureterostomy from the transplant kidney. Histological examination of the bladder revealed invasive high-grade urothelial carcinoma with micropapillary features with invasion into muscularis propria. Lymphovascular invasion was also noted. The bilateral native kidneys were atrophic with simple cysts and chronic inflammation. The prostate, bilateral seminal vesicles, vas deferens, and distal transplant ureter cuff were negative for tumor. Immunohistochemical staining of the tumor for SV40 antigen showed strong and diffuse staining. In contrast, immunohistochemistry for viral protein VP1 was negative. Molecular testing for BK virus by PCR for VP1 was positive. Immunohistochemistry for mismatch repair proteins showed normal, preserved expression. Identity testing confirmed that the tumor cells belonged to the patient and not to the donor. Conclusions: BK virus positivity has been reported in rare cases of urothelial carcinomas, mainly in adult transplant patients. To our knowledge, this is the first reported incidence of BK virus-associated urothelial carcinoma in a pediatric patient. Absence of late VP1 expression by IHC in conjunction with positive SV40 staining and positive BK virus PCR is consistent with a non-productive BK virus infection. Pathologists should be aware that identity testing should be considered in transplant patients with urothelial carcinoma to confirm the genetic origin of the tumor. Micropapillary differentiation may be a feature of BK virus-associated carcinoma.